STAT1 and STAT6 orchestrate Cbs transcription and transsulfur metabolism in microglia and contribute to parkinson’s disease-related neuroinflammation - Liu, Yang; Wang, Zhen; Ma, Ya-Ting; Chen, Yu-Xuan; Qian, Xin-Yi; Hou, Xiao-Ou; Wan, Bo; Ren, Hai-Gang; Hu, Li-Fang (Cellular and molecular life sciences : CMLS, 2025)
Microglia-mediated neuroinflammation is implicated in the pathogenesis of Parkinson’s disease (PD). Cystathionine β-synthase (CBS) and transsulfur metabolism modulate neuroinflammation. However, the regulation of Cbs transcription is poorly understood, and it remains unknown whether microglial CBS expression is affected by genetic factors in PD. Here, our in vitro study revealed that microglial CBS expression was downregulated by lipopolysaccharide (LPS)/interferon-γ (IFN-γ) but upregulated by interleukin (IL)-4/IL-13 stimulation. CBS and transsulfur metabolism not only inhibited inflammation but also promoted the anti-inflammatory transition of microglia. The mice with conditional microglial Cbs overexpression conferred resistance to LPS-induced neuroinflammation and dopaminergic neuron damage. A novel regulatory effect of the signal transducer and activator of transcription (STAT) family on Cbs transcription was identified: STAT1 as a suppressor, whereas STAT6 as an enhancer of Cbs transcription. PD-related gene DJ-1 knockdown (KD) decreased Cbs transcription through STAT1 activation in microglia. Moreover, Cbs overexpression alleviated the susceptibility of DJ-1 KD microglia to α-synuclein preformed fibrils (α-Syn PFFs) stimulation and the neurotoxicity to dopaminergic cells. Taken together, our findings reveal novel and opposite regulatory effects of STAT1 and STAT6 on microglial Cbs transcription in response to pro- and anti-inflammatory stimulation and demonstrate that CBS acts downstream of DJ-1, highlighting its role in PD.